DESPRE PĂDURE ŞI OMENIRE, PE PLANETĂ ŞI ÎN ROMÂNIA (PANGEEA, 2025)
About forest and humanity, on Planet and Romania. This paper is an essay about the place, role and importance of the forest in the current global society. It is the author's conception on forest issues, as an essential component of the biosphere and the environment.